Pengaruh Consumption Values terhadap Purchase Intention Pengguna Fitur Group Order pada Aplikasi Online Food-Delivery - Winda Khairunnisa; Diena Noviarini; Meta Bara Berutu (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The growth of Indonesia's digital ecosystem has driven the development of group order features on online food delivery platforms such as GrabFood, GoFood, and ShopeeFood, which allow users to place shared orders within a single transaction. This study aims to analyze the influence of consumption values (functional, emotional, social, and epistemic value) on self-identity and purchase intention among group order users, with self-identity positioned as both a mediating variable and a direct predictor of purchase intention. This research employed a quantitative approach with a causal associative design. Data were collected cross-sectionally from 210 respondents aged 18–35 in the Jabodetabek area through an online questionnaire, selected using purposive sampling, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that all four consumption values dimensions have a positive and significant effect on self-identity, with epistemic value as the strongest predictor, and on purchase intention, with social value as the most dominant predictor. However, self-identity was not found to significantly and directly affect purchase intention, indicating that usage intention is driven more by directly perceived, situational consumption values. As a conceptual implementation, this study also produced a group order application prototype named Bareng App.